The Forms of Cyberbullying Behavior among Teenage Students: A Systematic Literature Review - Yemima, Chrisanta Kezia (Jurnal Bimbingan dan Konseling Terapan, 2023)
This study aims to collect and analyze articles related to the various causes and forms of cyberbullying among adolescents in the age range of 13-19 years and to identify more deeply the forms of cyberbullying behavior. This study uses the SLR method, namely Systematic Literature Review. These results were carried out by analyzing 15 journals related to cyberbullying in adolescents with the Google Scholar electronic database and Publish or Perish with the keyword cyberbullying. The 15 journals were taken from previous forms of cyberbullying research in the range of 2017 to 2022 and filtered according to the intended category. There are various kinds of causes and forms of cyberbullying behavior in adolescents in the form of the development of social media which are increasingly developing in their forms, lack of information and assistance from those closest to them. The emergence of jealousy which is manifested by retaliation and approval of someone to be able to achieve that satisfaction. The forms of cyberbullying behavior that often occur in adolescents are Flaming, Harassment, Denigration, impersonation, Outing and Trickery.